Ingensalinae subfam. nov. (Hemiptera: Fulgoromorpha: Fulgoroidea: Inoderbidae), a new planthopper subfamily from mid-Cretaceous Kachin amber from Myanmar - C. Luo; C. Luo; Z. Song; X. Liu; X. Liu; T. Jiang; E. A. Jarzembowski; J. Szwedo (Fossil Record, 2022)
The second genus and species of recently established planthopper family Inoderbidae, Ingensala xiai gen. et sp. nov., is described based on a well-preserved specimen from mid-Cretaceous Kachin (Burmese) amber, and it can be definitely attributed to Inoderbidae mainly based on its head structure, pronotum, and mesonotum without median and lateral carinae and tegmen venation. Ingensala gen. nov. is superficially similar to Eofulgoridium regarding its venation pattern, rather than to the Inoderbidae type genus Inoderbe, and further confirmed that Inoderbidae might descend from the Jurassic planthopper family Fulgoridiidae. The early fork of CuA and the stem CuA bearing many branches also can be found in Jurassic Qiyangiricaniidae and Eocene Weiwoboidae. Ingensala gen. nov. also superficially resembles some Tropiduchidae: Tropiduchinae. The new genus differs from the type genus Inoderbe to a large extent according to its wide head, frons without fastigium, antennae not so elongate, the tectiform condition of wings' position in repose, large, broad and translucent tegmen, triangular basal cell, single CuA1, legs covered with short setae, and the lack of filamentous wax on body. Therefore, two new subfamilies (Inoderbinae stat. nov. and Ingensalinae subfam. nov.) are established for these two genera respectively. The diversification in planthoppers could be the result of pressure of environmental changes during the mid-Cretaceous, and Inoderbidae provides more information for us to understand the Cretaceous stage of Fulgoroidea evolution and diversification.